Effect of a fan on the unsteady distortion of s-duct intakes - Migliorini, Matteo; Zachos, Pavlos K.; MacManus, David G.; Giannouloudis, Alexandros (Association Aeronautique et Astronautique de France (3AF), 2024)
A key requirement for the integration of the propulsion and air induction systems is the assessment of the response of the fan to incoming flow distortion. This is especially crucial for the development of novel aircraft configurations with highly embedded engines. The recent advances in non-intrusive laser-based flow diagnostics increased the experimental capability to measure unsteady flows in convoluted intakes with high resolution in time and space. In the pathway to full-scale intake-engine tests, this work introduces the capability to successfully acquire non-intrusive high resolution flow distortion measurements in close proximity to a high-speed rotating fan. This also quantifies the impact of the fan on the inherent flow distortion of S-duct intakes. The measurements demonstrate that although the effect of the fan on the flow distortion is limited, the rotating blades can cause a local increase of the maximum levels swirl intensity at the blade tip region. Further development work on the ducted fan simulator is needed to operate the fan in the representative range of transonic rotors.